GLOSA DO WYROKU TRYBUNAŁU KONSTYTUCYJNEGO Z DNIA 27 LISTOPADA 2012 ROKU (SYGN. AKT U 4/12) - Walczuk, Konrad (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
In its judgment of 27 November 2012 (File Act no. U 4/12) The Constitutional Court has rightly concluded with reference to the so-called ritual slaughter that § 8. 2 Regulation of the Minister of Agriculture and Rural Development dated 9 September 2004 concerning the qualifications of persons entitled to the professional slaughter, and the conditions and methods of slaughter and killing of animals is incompatible with Art. 34 paragraph 1 and 6 of the Act of 21 August 1997 about Protection of animals, and by this Article 92 paragraph 1 of the polish Constitution. It should be emphasized that the judgment of the Court concerned essentially only formal issues beyond its scope, leaving the matter of the relationship between particular freedoms and rights (mainly human and civil), which imamy dealing with ritual slaughter. It is expected that these issues also will be subject to the substantive activities of the Constitutional Court.